Saltwater crocodile - Engkamat, Lading; Indraneil, Das (UNIMAS Publisher and Natural History Publications (Borneo) Sdn Bhd, 2023)
The Saltwater Crocodile (Crocodylus porosus) is the largest of all crocodilian species, with mature males reaching 7-metre and weighing over a tonne. Male crocodilians can grow larger and often faster than females, although in their natural environment, they reach sexual maturity at the same age. The species is distributed from the western coast of India, to the Andaman and Nicobar archipelago, south-east Asia, and southward to northern Australia and south Pacific.